Complete Remission Following Pembrolizumab in a Woman with Mismatch Repair‐Deficient Endometrial Cancer and a Germline BRCA1 Mutation. (22nd February 2018) - Dizon, Don S.; Dias‐Santagata, Dora; Bregar, Amy; Sullivan, Laura; Filipi, Jennifer; DiTavi, Elizabeth; Miller, Lucy; Ellisen, Leif; Birrer, Michael; DelCarmen, Marcela
Abstract : : Endometrial cancer is the most common gynecologic malignancy in the U.S. and, although the majority of cases present at an early stage and can be treated with curative intent, those who present with advanced disease, or develop metastatic or recurrent disease, have a poorer prognosis. A subset of endometrial cancers exhibit mismatch repair (MMR) deficiency. It is now recognized that MMR‐deficient cancers are particularly susceptible to programmed cell death protein 1 (PD‐1)/programmed death‐ligand 1 (PD‐L1) inhibitors, and in a landmark judgement in 2017, the U.S. Food and Drug Administration granted accelerated approval to pembrolizumab for these tumors, the first tumor‐agnostic approval of a drug. However, less is known about the sensitivity to PD‐1 blockade among patients with known mutations in double‐strand break DNA repair pathways involving homologous recombination, such as those in BRCA1 or BRCA2 . Here we report a case of a patient with an aggressive somatic MMR‐deficient endometrial cancer and a germline BRCA1 who experienced a rapid complete remission to pembrolizumab. Key Points : Endometrial cancers, and in particular endometrioid carcinomas, should undergo immunohistochemical testing for mismatch repair proteins. Uterine cancers with documented mismatch repair deficiency are candidates for treatment with programmed cell death protein 1 inhibition. Genomic testing of recurrent, advanced, or metastatic tumors may be useful to determine whether patients are candidates for precision therapies. Abstract : Endometrial cancer is the most common gynecologic malignancy, accounting for more than 60, 000 newly diagnosed cases in the United States. Most cases present at an early stage and can be treated with curative intent; however, those who present with advanced disease or who develop metastatic or recurrent disease, have a poor prognosis. Active standard treatments have been identified in the first‐line or adjuvant settings; however, therapeutic options are limited for second‐ or later‐line treatment of the disease. This has prompted interest in molecular testing, particularly for women with recurrent, advanced, or metastatic endometrial cancers.